1991
DOI: 10.1039/jm9910101027
|View full text |Cite
|
Sign up to set email alerts
|

New antimonate–vanadate with the rutile structure

Abstract: VCrSbO, has been prepared and its magnetic and electronic properties investigated. The crystal structure was refined from X-ray powder diffraction by the Rietveld method. The unit cell is tetragonal (space group P4,/rnnm, Z=2), a=4.5708(4) A and c=3.0281(3) A. The compound is isostructural with the rutile phase FeNbO, and stoichiometric with respect to all three constituent metals atoms. The electron diffraction pattern is consistent with a tetragonal symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Very often the catalytic, magnetic, optical and electrical properties can be modified by changing some of the cations in the rutile structure. Tetragonal compounds M 1 M 2 SbO 6 (where M 1 = Cr, Rh and M 2 = Ru, V, Ti, Te, Ge, Sn) with rutile-type structures have been obtained and characterized recently [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Very often the catalytic, magnetic, optical and electrical properties can be modified by changing some of the cations in the rutile structure. Tetragonal compounds M 1 M 2 SbO 6 (where M 1 = Cr, Rh and M 2 = Ru, V, Ti, Te, Ge, Sn) with rutile-type structures have been obtained and characterized recently [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with general formula M MSbO 6 , where M = Fe, Cr, Al; M = V, Ru, Ti have been reported and characterized recently because of their interesting electrical, magnetic and catalytic properties [17]. Among these FeVSbO 6 and CrVSbO 6 are isostructural and crystallize in the tetragonal system and possess a rutile-type structure (space group P 4 2 /mnm, Z = 2) [1,4,5]. A new solid solution with chemical formula Fe 1−x Cr x VSbO 6 forms also a tetragonal structure of rutile-type in the whole components concentration range (0.0 < x < 1.0) of the FeVSbO 6 CrVSbO 6 system [8].…”
mentioning
confidence: 99%
“…The temperature dependence of magnetic susceptibility of CrSbVO 6 has demonstrated that the magnetic properties depend only on the crystal structure and the oxidation states of the cations involved in this compound [3]. These results have proved that CrSbVO 6 is a paramagnet and a classical semiconductor.…”
Section: Introductionmentioning
confidence: 91%
“…According to Ballarini et al when the (Cr + V)/Sb ratio is about 2 in the Cr-Sb-V-O system a compound with the formula Cr 3+ Sb 5+ V 4+ O 6 is formed [1,2]. Isasi et al has shown that CrSbVO 6 can be synthesized by heating (in evacuated silica glass tubes) a mixture of Sb 2 O 5 , Cr 2 O 3 and V 2 O 4 at 1163 K for 24 h [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation